Matlab-Based Control Simulation For Increasing The Power Capacity Of Geothermal Power Plants - Siagian, Parlin; Alam, Hermansyah; Putra, Randi Rian; Tanjung, Munawar Sajali (LPPJPHKI Universitas Dehasen Bengkulu, 2025)
Geothermal Power Plant (PLTP) is a renewable energy source that has great potential to meet electricity needs in a sustainable manner with low carbon emissions. This research aims to develop mathematical models and Matlab-based control systems to increase the power capacity of geothermal power plants. The system model includes reservoir dynamics, production wells, turbines, and generators with control using the PID (Proportional-Integral-Derivative) method. Simulations were conducted to test the system response to variations in electrical load, reservoir temperature, and operational disturbances. The simulation results show that the PID control successfully maintains the electrical power output to be close to the reference value with a fast response despite the presence of overshoot and initial oscillation. Adjustment of PID parameters is recommended to reduce overshoot and accelerate stabilisation of power output. This research contributes to the optimisation of geothermal power plant operation so as to improve efficiency and national energy security based on geothermal energy.